Chapter Final Remarks - xxxxx, xxxx (Taylor & Francis, 2021)
sorption materials water remediation materials for environmental remediation heavy metal removal sorption of radionuclides
English
Keywords: Materials science; sorption materials; water remediation; materials for environmental remediation; heavy metal; removal sorption of radionuclides